2006
DOI: 10.1021/ie060968p
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Carbonaceous Solids on Different Substrates from Thermal Stressing of JP-8 and Jet A Fuels

Abstract: Carbon deposition from jet fuel on metal surfaces will create problems for the operation of future aircraft. Two jet fuel samples (Jet A and JP-8) were heated in a glass-lined flow reactor in the presence of metal and nonmetal substrates placed in the fuel path. The solid deposits collected on the substrates were examined using scanning electron microscopy (SEM) with energy-dispersive X-ray spectroscopy (EDS) and by temperature-programmed oxidation (TPO). The nature and amount of carbonaceous deposits from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 21 publications
3
71
1
Order By: Relevance
“…Therefore, aviation fuel is subject to thermal stress in the flow path between the aircraft fuel tanks and the combustion chamber. High thermal loads can lead to temperatures as high as 500 °C on metallic surfaces in the fuel delivery system of advanced aircraft [17,18]. This heat leads to the formation of insoluble deposits which can plug the narrow passageways found in fuel systems and in extreme cases, lead to component failure.…”
Section: Thermal Stressing Of Aviation Fuelmentioning
confidence: 99%
“…Therefore, aviation fuel is subject to thermal stress in the flow path between the aircraft fuel tanks and the combustion chamber. High thermal loads can lead to temperatures as high as 500 °C on metallic surfaces in the fuel delivery system of advanced aircraft [17,18]. This heat leads to the formation of insoluble deposits which can plug the narrow passageways found in fuel systems and in extreme cases, lead to component failure.…”
Section: Thermal Stressing Of Aviation Fuelmentioning
confidence: 99%
“…It was also reported that stainless steel tubes formed more deposits than aluminum tubes [16] probably due to the catalytic behavior of iron and iron-based alloys during carbon oxidation [33].…”
Section: Formation Of Solid Depositsmentioning
confidence: 97%
“…It has been suggested that the nature and amount of solid deposition from the thermal decomposition of jet fuel were dependent on the substrate properties and jet fuel composition [33]. It was also reported that stainless steel tubes formed more deposits than aluminum tubes [16] probably due to the catalytic behavior of iron and iron-based alloys during carbon oxidation [33].…”
Section: Formation Of Solid Depositsmentioning
confidence: 99%
“…The alkene selectivities of Cat3, Cat4 at 650 • C are almost equals to 700 • C, and they have a sharp decrease at 750 • C. The addition of Cat3, Cat4 not only enhanced the rates of cracking reaction, but also improved the alkene selectivity of cracking reaction based on the increasing of the probability of cracking reaction with the mechanism of carbenium ions. The unstable carbenium ions are easy to occur the ␤-scission to generate alkenes [18,19].…”
Section: The Gas Phase Distribution and The Ratio Of Alkene To Alkanementioning
confidence: 99%